Development and Implementation of a Survey to Assess Health-Care Provider's Competency, Attitudes, and Knowledge About Perinatal Palliative Care. Issue 3 (July 2019) - Stenekes, Simone; Penner, Jamie L.; Harlos, Michael; Proulx, Marie-Claude; Shepherd, Erin; Liben, Stephen; Thompson, Genevieve; MacConnell, Grace; Grégoire, Marie-Claude; Siden, Harold (Hal)
Perinatal palliative care is an emerging area of health care. To date, no published tools assess health-care provider's knowledge and level of comfort in providing such care. A 2-phase study was undertaken to develop and implement a survey to evaluate the self-assessed competency, attitudes, and knowledge of health-care providers working in perinatal palliative care. Phase 1 included a review of the literature and appraisal of palliative and death-related instruments to inform the initial draft of the Perinatal Palliative Care Survey (PPCS). Twenty-four Canadian pediatric palliative care specialists critiqued the PPCS, establishing its face and content validity. Phase 2 involved administering the PPCS at 4 sites across Canada, resulting in 167 responses from nurses, physicians, and midwives. The majority of participants responded that they possessed a degree of comfort in providing perinatal palliative care, particularly with assessing pain (76%), managing pain (69%), assessing other symptoms (85%), and managing other symptoms (78%). Two areas where participants level of confidence or extreme confidence was diminished included having conversations with families about the possibility of their infant dying (55%) and knowing and accessing community palliative care resources (32%). Responses in the knowledge section identified gaps related to opioid use, pharmacological interventions for breathlessness, pain behaviors, and tolerance developed to opioids and sedatives. Eighty-six percent of respondents stated that if education about palliative care was made available, they would participate with priority topics identified as communication with families (75%), managing symptoms (69%), pain management (69%), and ethical issues (66%). The PPCS provides a useful assessment to determine the educational needs of health-care providers delivering perinatal palliative care.